The Impacts of Heatwaves on Antimicrobial Resistance and Public Health: A Pitch - Yen Nee Teo; Elizabeth Yong (Journal of Accounting and Management Information Systems (JAMIS), 2024)
This pitching research letter (PRL) applies the systematic 2-page pitch template developed by Faff (2021, 2015) to organise a future PhD research topic regarding the effects of heatwaves on antimicrobial resistance and public health. By adhering to the template, it helps researchers to extract the succinct information required by a research proposal. The thoughtful design of the template renders it an invaluable tool for novice researchers in developing a new research plan and communicating it in an organised and structured manner.
Keywords: I18; Q54; Q57; 650; Pitching research; heatwaves; antimicrobial resistance; public health